A model for destination branding of iconic architectural tourist attractions in Bali, Indonesia - Dinar Sukma Pramesti; Dwi Novita Cahyaningtyas Permatasari; Ong Chuan Huat (Borneo Novelty Publishing, 2026)
Purpose – This study aims to explore the potential of architectural tourist attractions in Bali, with particular emphasis on the diversity of traditional and contemporary architecture as part of cultural tourism experiences.Design/Methodology/Approach – The research adopts a qualitative approach, utilizing in-depth interviews with tourists and tourism stakeholders, complemented by a review of relevant literature to understand perceptions and the role of architecture in destination appeal.Findings – The findings indicate that tourists demonstrate a strong interest in architecture as a key component of cultural experiences. The study proposes a destination branding model, The Wonder of Architectural Diversity, supported by the 4A framework (Attractions, Amenities, Ancillary, Accessibility) and the STAR model (Storytelling, Event Tourism, Activities, and Reviews), to enhance destination attractiveness. Additionally, strengthening architectural promotion through cultural festivals, integrating traditional elements into modern developments, and improving supporting amenities are identified as crucial strategies to broaden tourist appeal.Originality/Value – This study contributes to tourism and destination branding literature by highlighting architecture as a strategic asset in cultural tourism development. It offers a novel integrative model that combines branding and tourism frameworks to enhance destination competitiveness while preserving cultural identity.